COPD cases detected by spirometry on world COPD day event in Bursa - Sengoren Dikis, Ozlem; Us Dulger, Seyhan; Karadag, Mehmet; Demirci, Hakan (The European Research Journal, 2015)
Objective. We organized a ‘World Chronic Obstructive Pulmonary Disease (COPD) Day’ event to raise awareness in society of the disease and we evaluated the results of the activity. Method. Volunteers (n= 79) consisted of persons shopping in a famous shopping center in Bursa. A short past history of COPD from the volunteers was requested. Pulmonary Function Tests were performed by spirometry and a Fagerstrom test for dependence was filled out by the volunteers. In cases where airway obstruction was detected, physicians performed a reversibility test. Results. Of the 79 volunteers who participated in the study, 39 cases were detected to have airway obstruction. Of those, 15 patients had been previously diagnosed with COPD; on the other hand, 24 patients were diagnosed with COPD for the first time. There was no newly diagnosed COPD patient among the nonsmokers. The prevalence of COPD was 49.36% and the awareness rate was only 38.46%. Conclusion. In the present study, we determined that the COPD prevalence is 49.36%, which is quite high when compared with the previous studies published in Turkey. In such a cross sectional study, volunteers would probably be composed of persons who would have the disease at higher rates. We observed that there was a low awareness of COPD among smokers. Events that are aiming to increase the social awareness to such a particularly prevalent disease should be encouraged.